1996
DOI: 10.1080/758525514
|View full text |Cite
|
Sign up to set email alerts
|

Is the Fisher effect robust? Further evidence

Abstract: New international evidence exists on the Fisher effect in the United States, the United Kingdom, Japan, Germany and Canada over the modern (post-March 1973) floating exchange rate experience. Some puzzling data has been observed which suggests that the Fisher effect appears to be strong only for particular sample periods. It has also been reported in the literature that the Fisher effect is more likely in the long run, and that it is not common across economic regimes. This study sheds some light on these cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 11 publications
1
19
0
1
Order By: Relevance
“…In contrast, Mishkin [29], has confirmed a strong long-run Fisher effect, but no evidence of the short-run Fisher eflfect for the US. Besides, Yuhn [42] has reported that the Fisher effect is strong over long horizons, but there is a confirmation of a short-run Fisher effect detected in Germany.…”
Section: Chapter 2 Literature Reviewmentioning
confidence: 96%
See 3 more Smart Citations
“…In contrast, Mishkin [29], has confirmed a strong long-run Fisher effect, but no evidence of the short-run Fisher eflfect for the US. Besides, Yuhn [42] has reported that the Fisher effect is strong over long horizons, but there is a confirmation of a short-run Fisher effect detected in Germany.…”
Section: Chapter 2 Literature Reviewmentioning
confidence: 96%
“…In addition to that, Yuhn [42] has found a strong long-run Fisher effect for Germany, US, and Japan, but no noticeable evidence was found for UK, and Canada.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The Fisher hypothesis has been validated by Garcia (1993) for Brazil, Thornton (1996) for Mexico, Payne and Ewing (1997) for Malaysia, Pakistan and Sri Lanka, and Atkins and Coe (2002) for US and Canada. Yuhn (1996) found evidence supporting the Fisher effect in US, Germany and Japan, but little evidence of it in UK and Canada. Inder and Silvapulle (1993) did not find evidence in favor of the Fisher effect in Australia.…”
Section: Introductionmentioning
confidence: 98%